Optimizing the Da'wah Communication of the Indonesian Ulema Council as a Mediator of Anti-War Sentiment and World Peace - Tsulasy Fadhil; Hanif; Dedeng Wiraha; Siti Nuri Nurhaidah; Ahmad Irfan (Quality : Journal Of Education, Arabic And Islamic Studies, 2026)
The ongoing armed conflicts in various parts of the world place religious institutions in a strategic position as agents of peace. The Indonesian Ulema Council (Majelis Ulama Indonesia—MUI), as the highest Islamic fatwa authority in Indonesia, possesses the capacity to serve as both a moral mediator and a global peace communicator. This article examines how MUI can optimize its da'wah communication strategy to build and strengthen anti-war sentiment among the Indonesian Muslim society and the international Islamic community. Utilizing a qualitative approach based on literature studies and policy document analysis, this research explores the theoretical framework of da'wah communication, faith-based conflict resolution theory, and MUI's track record of involvement in global peace issues. The research findings indicate that MUI holds significant potential as a moral diplomacy actor, yet it faces several structural and communicative obstacles that need to be addressed systematically. The proposed strategies include transforming da'wah mediums toward digital platforms, strengthening networks among international religious institutions, and formulating peace narratives rooted in the values of Islam as rahmatan lil 'alamin (a mercy to all creation). This study contributes to the development of contemporary da'wah communication theory and the practice of religious diplomacy within a global context.